Youth engagement in flood disaster management in Malaysia - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Noor Amira Syazwani, Abd Rahman; Ju, Soon Yew (Human Resource Management Academic Research Society (HRMARS), 2022)
Most countries worldwide acknowledge the importance of youth in driving the country forward in terms of politics, society, and the economy. This group is known for its enthusiasm, energy, and ability to make sound decisions. Their involvement in flood disaster management is critical to the well-being of flood victims. The fact that countries have enlisted the help of youth in flood disaster management is not surprising. Flood disaster management requires youth involvement to construct an all-encompassing plan that meets countries' demands. Some youths, however, fail to make use of their unique position to get involved in flood disaster response efforts. Research on youth's abilities and contributions as change agents in their communities has been scant, despite the benefits of their involvement in disaster risk reduction (DRR). Therefore, this study will investigate Malaysian youth participation in flood disaster management. This qualitative research examines and analyses papers from various sources, including journal articles, newspaper articles, and government documents. The findings revealed that most Malaysian youths were actively involved in flood disaster management, particularly during and after a flood. As part of the assistance provided, funds were raised, the victim's house was cleaned up, food and clothing were provided, and the flood victims were rescued. This study contributes to enriching knowledge on youth in flood disaster management. The findings of this study will help policymakers formulate sound public policies and programs to encourage youth to participate in flood disaster management.